University iTutoring: An empowerment tool during the covid-19 - Secanilla Campo, Esther (2022)
Given the current emergency situation due to the Covid-19 pandemic, it is essential to address new strategies to carry out university teaching. In this university experience, on teaching practice in different universities, we aim to disseminate and apply university tutoring as a fundamental tool to face current challenges. The authors have coined the term iTutoría Universitaria (University iTutoring) as a proposal of excellence, in terms of the accompaniment of students and the emotional support that it carries implicitly. Preliminary results reflect that further work and research is needed in order to make interventions more tailored to the needs of each university context.